PENGARUH PROFITABILITAS, LEVERAGE KEUANGAN, DAN LIKUIDITAS TERHADAP KETEPATAN WAKTU PELAPORAN KEUANGAN (Perusahaan Manufaktur di Bursa Efek Indonesia) - Shelly F Kartasari (AKUNTABILITAS, 2012)
The objectives of this research are 1) to analyze the influence of profitability, financial leverage and liquidity of financial reporting timeliness of manufacturing companies listed on the Indonesia Stock Exchange and 2) discuss whether the profitability, financial leverage, and liquidity affect the timeliness of the company's financial reporting. Samples used in this research of 72 manufacturing companies listed on the Indonesia Stock Exchange 2008-2010 period. Data to be used is the research was secondary data. Data regarding the timeliness of the date of submission of financial statements and other data from the idx and ICMD. Techniques of analysis in this research using logistic regression. Research finding has shown that during period of years 2008-2010, the timeliness of manufacturing companies listed on the Indonesia Stock Exchange is very high (75.00%). The result of the research also found that the profitability effect on timeliness of corporate financial reporting, while financial leverage and liquidity do not affect the timeliness of corporate financial reporting. Keywords : Timeliness, financial statements, profitability, financial leverage, liquidity